Dinamika Fraktal dalam Pertumbuhan Kristal Logam untuk Inovasi Material Baru - Taufiq Dalming; Asyari Al Hutama Azis (Journal of New Trends in Sciences, 2024)
Fractal structures play a crucial role in improving material properties due to their unique self-similar geometries. These geometrical patterns exhibit repetition at multiple scales, which can enhance surface area, strength, and other mechanical characteristics. This study investigates the influence of fractal patterns on the crystal growth and mechanical performance of metallic materials, focusing on strength, toughness, and hardness. Using a combination of computer simulations and laboratory experiments, the research models metal crystal formation under controlled conditions, where fractal characteristics are introduced through diffusion-limited aggregation (DLA) and electrodeposition methods. The findings reveal that embedding fractal patterns into the crystal growth process can increase material strength by approximately 20% compared to conventionally structured metals. This improvement is attributed to the efficient stress distribution within the fractal geometry, which minimizes stress concentration points and enhances resistance to fracture. Additionally, materials with fractal-based microstructures exhibit better toughness and deformation resistance, improving durability under mechanical load. The study also examines the underlying mechanisms of these effects, emphasizing the role of fractal-induced microstructural control in optimizing material integrity. These results demonstrate the significant potential of fractal-based material design in engineering stronger, lighter, and more flexible metallic components. The research contributes to the broader understanding of how geometric complexity can be harnessed to develop advanced materials for applications in construction, automotive manufacturing, and flexible electronics, thereby supporting the development of next-generation high-performance materials.